2002
DOI: 10.1179/026708302225001697
|View full text |Cite
|
Sign up to set email alerts
|

Transient liquid phase bonding of a microduplex stainless steel using amorphous interlayers

Abstract: Microduplex stainless steels are two phase alloys which show excellent corrosion resistance and toughness. In order to join these special steels, fusion welding processes are normally used and a second post-weld heat treatment is necessary to regain the original ferrite to austenite ratio. In this study, transient liquid phase diffusion bonding was used to join a 2205 duplex stainless steel with the aid of amorphous interlayers. The research compares a Ni ± B ± Si ternary system with that of an Fe ± B ± Si int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The joint is held at the bonding temperature until the melting point depressants are lost from the liquid interlayer by diffusion and the liquid interlayer solidifies isothermally due to the change in composition of the bond. This technique has been previously used to join different alloy systems including duplex stainless steels [23][24][25][26][27][28][29]. Figure 1 is a schematic picture of the steel plates-metallic glass assembly used in this work.…”
Section: Microchannel Reactormentioning
confidence: 99%
“…The joint is held at the bonding temperature until the melting point depressants are lost from the liquid interlayer by diffusion and the liquid interlayer solidifies isothermally due to the change in composition of the bond. This technique has been previously used to join different alloy systems including duplex stainless steels [23][24][25][26][27][28][29]. Figure 1 is a schematic picture of the steel plates-metallic glass assembly used in this work.…”
Section: Microchannel Reactormentioning
confidence: 99%
“…3,4 Some studies have reported that they are as strong as the base material or even stronger, causing the failure in the base material rather than in the joint. [5][6][7] Over the past few decades, the diffusion soldering process has been used for die-attach purposes such as Cu/Sn, Ni/Sn and Au/Sn. [8][9][10] One of the good candidates of TLP bonding for die-attach is indium (In) which can also be applied as a joining material due to its low melting temperature in forming high melting intermetallic compounds (IMC).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] . These ller metals can be applied in forms of powders, powder-based pastes, rolled plates or tapes, or Metglas ® amorphous brazing foils (designated as MBF) [8][9][10][11][12][13][14] . The amorphous brazing foils made by rapid solidi cation have been used predominantly due to many advantages such as the amorphous structure with uniform composition and homogeneous phase state, a narrow temperature interval of melting point, a short brazing time and high atom diffusion rate 9,15,16) , thus homogeneous brazing joints can be obtained.…”
Section: Introductionmentioning
confidence: 99%